(untitled) (Journal of Medical & Health Sciences Review, 2025)
Researchers’ interest in the idea of an ethical climate in the nursing setting, and more especially, how it relates to job satisfaction, has grown over the last 20 years (Koskenvuori et al., 2019). An important area to investigate is how the ethical climate at Tertiary care Hospital Multan affects the job satisfaction of Post RN nurses. The ethical climate in healthcare settings has a significant impact on Post RN nurses’ job satisfaction. This study therefore aims to investigate the impact of ethical climate on job satisfaction among Post RN nurses in Tertiary care Hospital Multan. To assess the impact of ethical climate on job satisfaction among Post RN nurses. The proposed study was conducted in Tertiary care Hospital. All nurses of Post RN in a Tertiary care Hospital Multan were population for data collection. A descriptive cross- sectional study was conducted to check the impact of ethical climate on job satisfaction among Post RN nurses in selected hospital. A sample size of 30 Post RN nurses were targeted from hospital. Data collected through the adoptive questionnaire that contains close ended questions. Data was analyzed and interpreted statistically on SPSS. The result finding from the data indicates that the majority of respondents (73%) agreed or strongly agreed. A smaller portion (13.3%) remained neutral while only (13.3%) either disagreed or strongly disagreed. There is evidence to support the concept that Post RN nurses’ job satisfaction is positively impacted by ethical climate. Hence it was proved through this research that ethical climate does have positive impact on job satisfaction among Post RN nurses. Therefore it is recommended to promote ethical leadership and to communicate clear ethical polices to nursing staff of the organization. So it is important to recognize and reward ethical behaviors.